Mutational analysis of HOXA10 gene in Chinese patients with cryptorchidism. (25th April 2016) - Cheng, Z.; Wang, M.; Xu, C.; Pei, Y.; Liu, J. C.; Huang, H.; He, D.; Lu, P.
Summary: Cryptorchidism is one of the most common congenital anomalies and affects 2–4% of full‐term new born boys. Its aetiology is poorly understood at present. HOXA10 plays a pivotal role in regulation of testicular descent. Male mice mutant for Hoxa10 exhibit unilateral or bilateral cryptorchidism as a result of impaired development of the gubernaculums. In this study, we performed mutation analysis of HOXA10 gene in a cohort of 98 cryptorchid patients. And we found a mutation (N27K) in a boy with unilateral cryptorchidism. The mutation was not detected in 106 healthy controls. Both in silico analyses and functional studies showed that the mutation affected the function of HOXA10. The results demonstrated that mutation in HOXA10 gene contributes to the pathogenesis of cryptorchidism, but may not be a common cause.